Structure and performance of electroblown PVDF-based nanofibrous electret filters - POLAT, YUSUF (WILEY, 2020)
Poly(vinylidene fluoride) (PVDF)-based nanofibrous mats were produced via electrically assisted solution blowing (electroblowing). Morphology and filtration properties of the nanofibrous mats were investigated as a function of polymer concentration and applied voltage. The average fiber diameter was reduced from 727 +/- 366 nm to 408 +/- 143 nm and from 424 +/- 233 nm to 328 +/- 105 nm, using 16 wt% and 12 wt% concentrations, respectively, with an increase of electric voltage from 0 to 30 kV. In addition, the pore size of the mats produced from 12 wt% concentration decreases with the increase of electric voltage. Results showed that electroblown mats possess high filtration properties and performance. Enhancement of mechanical capturing efficiency is attributed to the reduction in fiber diameter and pore size. The enhancement of electrostatic capturing efficiency is thought to be from the improved electret property of the mats, which eliminates the need for a second step to polarize nanofibrous mats. As a result, both mechanical and electrostatic capture efficiency of the mats is enhanced compared to solution blown PVDF mats. The emerging electret property might be due to the accumulation of the electrostatic charges at high voltage and the enhanced polarized beta phase, which is the result of the high drawing ratio applied to the polymer jet during the spinning process.
Keywords: electret filter; electroblowing; nanofibrous membrane; ELECTROSPUN POLYVINYLIDENE FLUORIDE; FILTRATION EFFICIENCY; AIR FILTRATION; FIBERS; MEMBRANES; NANOPARTICLES; PARAMETERS